Retrograde femoral nailing of periprosthetic fractures around total knee replacements. Issue 2 (February 2016) - Jones, Mark D.; Carpenter, Charlotte; Mitchell, Stephen R.; Whitehouse, Michael; Mehendale, Sanchit
Abstract: Introduction: The incidence of primary total knee replacement (TKR) is increasing with a resultant rise in those patients sustaining distal femoral periprosthetic fractures around TKRs. The management of these fractures pose a significant challenge. The compatibility of retrograde femoral intramedullary (IM) nails with femoral TKR components needs to be considered preoperatively when this complex pathology is addressed. The aim of this study was to update the literature and assess the compatibility of the most commonly used primary TKR prostheses and retrograde femoral IM nails using a Sawbone anatomical model. Methods and materials: Eight of the most commonly used primary TKR prostheses and four of the most commonly used retrograde femoral IM nails were identified. The femoral components of the TKRs were implanted onto left sided femoral Sawbones using the manufacturer's guides and cutting blocks and positioned appropriately. The retrograde IM nails were inserted using the conventional entry point and a nail was deemed compatible if this was possible through the femoral prosthesis. Details of whether a posterior entry point was required to allow insertion, whether the femoral nail was scratched by the femoral TKR prosthesis on insertion and whether excess force was required to insert the retrograde femoral IM nail were recorded. Results: The Biomet AGC Cruciate Retaining (CR) and Posterior Stabilised (PS) TKR were the only prostheses that were compatible with all the nails used. The other TKR prostheses were not compatible because of the force required to gain entry, scratching of the retrograde femoral IM nail or because a posterior entry point was required to gain entry through the intercondylar notch. Conclusion: The majority of standard sized retrograde femoral nails are technically feasible for insertion through most femoral TKR components but this study has found that they are not compatible due to excessive force required for insertion, damage to the nail during insertion or the risk of anterior cortex perforation. Further studies are required to update the compatibility table and cadaveric studies would confirm the findings and allow further mechanical testing.